Semiconductor Materials for Solar PV Technology and Challenges towards Electrical Engineering. (21st August 2022) - Siva Ramkumar, M.; Felshiya Rajakumari, R.; Kannan, Nithiyananthan; Premkumar, R.; Mohanasundaram, S.; Purushotham, S.; Ramya, D.; Rajan, Kavitha
Abstract : The contemporary concern in worldwide power scenario and consumption rate is frightening significantly at a marvelous amount of population, and it originates a very high augment in the electrical energy area. The all-embracing attraction and manufacture of fossil energy is the chief reason in the ecological issues. Due to these relic fuels, the ecological resources get exhausted, and it results in climatic change. Due to these negative aspects, every country puts effort to bring the energy efficiency high with the help of renewable energy. Presently, the solar energy donation worldwide decreases. Contrarily, solar energy contribution to the global energy is highly contrary to nonconventional energy resources. But there is a progress in power generation, and it plays a vital role in solar photovoltaic generation. Gallium nitride and silicon carbide power semiconductors will emerge to bring the efficiency high in the photovoltaic technology. In this work, we will converse about how to increase the efficiency by using gallium nitride.